U.S. Survey of factors associated with adherence to standard of care in treating pregnant women with opioid use disorder. (2nd January 2020) - Howard, Heather Grimshaw; Freeman, Katherine
Abstract: Objective: To identify, factors associated with obstetricians' treatment recommendations for pregnant women with an opioid use disorder (PWOUD), and to determine the prevalence of physicians waivered for buprenorphine as a medication-assisted treatment (MAT). Methods: We conducted a structured online survey of a nationally representative sample of 565 obstetrical physicians, with a response rate of 38%. Logistic regression models were derived to identify factors that influence treatment recommendations for PWOUD. The Clopper–Pearson method was used to derive the confidence interval (CI) for the number of physicians waivered for buprenorphine. Results: Approximately 77% of respondents had provided care for a PWOUD within the last year. Physicians reported that at least 75% of their PWOUD received Medicaid for prenatal care. The most common opioids used at patient presentation were prescription opioids, with the second most common being methadone. A total of 14.0% had buprenorphine waivers (95% CI: 11.6–16.7%), and among those waivered, 47% prescribed buprenorphine to PWOUD. Factors associated with buprenorphine waiver encompass referrals to community support services. The three most prominent factors associated with adherence to standard of care were: type of opioid at presentation, patient's choice, and physician's experience. Type of opioid was associated with methadone presentation, socioeconomic status, shared decision making and practice setting. Patient's choice was associated with physician preparedness and practice duration. Physician's experience was associated with referral to recovery-oriented services. Conclusions: Novel interventions are needed to (1) promote office-based treatment for opioid use disorder through continuing medical education, (2) provide physicians with access to recovery-oriented resources and (3) increase patient autonomy in healthcare decision making. These proposed evidence-based interventions will promote best practices for women and their infants and greater accessibility to standard of care.